What has project characteristics got to do with the empowerment of individuals, teams and organisations?. Issue 3 (2nd May 2018) - Tuuli, Martin Morgan
Abstract : Purpose: The purpose of this paper is to explore the impact of project settings on empowerment experiences of individuals and teams by examining the effects of specific project characteristics on facets of the empowerment concept (i.e. the structural and psychological perspectives). Design/methodology/approach: A parallel questionnaire survey of client, consultant and contractor organisations was conducted in Hong Kong to test hypotheses relating three facets of the empowerment concept and five project-level antecedents. Hierarchical linear modelling and ordinary least square regression were employed to test the hypotheses. Findings: The analyses show that dynamic project environments, high project team integration and high interdependence of project tasks lead to high individual psychological empowerment, while public-client projects (compared with private-client projects), a hostile project environment and high client integration lead to a low individual psychological empowerment. Uncertainty in project technology also leads to high team psychological empowerment, while hostile project environments lead to low team psychological empowerment. Further, dynamic project environments lead to more empowering work climate, while hostile project environments lead to less empowering work climate. However, project team integration, project complexity, project lifecycle and quasi-public-client projects (compared with private-client projects) have no significant association with the empowerment of individuals and teams. Originality/value: This study examined task-related factors (i.e. project in this case) which traditionally have not been the focus of studies examining the antecedents of empowerment. Further, project-level antecedents and their link to an integrated perspective of empowerment comprising a sociostructural perspective, a psychological perspective and a team-based perspective are examined, which is a significant departure from the unitary perspective of empowerment taken in most previous studies.